Subject support in collection development: using the bibliometric tool - Yeoh, K.H.; Kaur, K. (2008)
Purpose - The purpose of this paper is to examine the publication output of Research in Higher Education for subject support in collection development in the light of growing interest in diversified domains of research in higher education. Design/methodology/approach - The paper presents a quantitative analysis of 202 articles published in Research in Higher Education from 2000 to 2005. It employs bibliometric analysis to investigate the publication distribution, authorship patterns, research collaborations among scholars, and citation analysis to profile surrogated information for higher education resource management. Findings - Analysis of 40 issues of publications revealed a diversified usage pattern of bibliographic reference sources by contributing researchers, with a cumulative total of citations being 8,374. A positive trend in research collaboration of contributing authors, and a steady growth in the use of reference sources, periodicals and web documents in the citations signify the trend of scholarly communication of research works in the electronic age. Similar to other disciplines of research findings, journals and books were the most cited source materials for researchers discussed. Originality/value - This paper serves as a window to understanding the scientific productivity of contributing scholars, specifically in the field of higher education. This may assist researchers' and stakeholders' collection management decisions, and provide a referencing source for library professionals and policy makers.